1992
DOI: 10.1007/bf02635905
|View full text |Cite
|
Sign up to set email alerts
|

The influence of food emulsifiers on fat and sugar dispersions in oils. I. Adsorption, sedimentation

Abstract: The adsorption isotherms of several emulsifiers to fat and sugar crystals dispersed in oils have been determined. Further, the influence of the emulsifiers on the interactions between the crystals has been estimated in sedimentation experiments, where an increased sediment volume due to adsorption corresponds to an increased adhesion between the crystals and vice versa. Most of the emulsifiers examined adsorb weakly to fat crystals and form tight monolayers, resulting in increased adhesion between the crystals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 22 publications
6
58
0
Order By: Relevance
“…The competitive adsorption of lecithin to displace proteins adsorbed at the oil/water interface may cause a change in the interactions between the proteins and fat crystals and thus affect the mechanical strength of the interfacial film [Ogden & Rosenthal, 1997], while the competitive adsorption of lecithin to displace proteins adsorbed at the surface of fat crystals may facilitate the coalescence of fat globules and thus destabilise the emulsions [Melsen & Walstra, 1989]. The adsorption of lecithin may also change the polarity of fat crystals [Johansson & Bergenståhl, 1992;Rousseau, 2000]. Usually, low-molecular-weight surfactants are effective at generating emulsions with smaller droplets because of their fast adsorption to the newly created interfaces, but they may not be effective at providing long-term stability to the emulsions.…”
Section: Use Of Soy Lecithin In Combination With Other Additivesmentioning
confidence: 99%
“…The competitive adsorption of lecithin to displace proteins adsorbed at the oil/water interface may cause a change in the interactions between the proteins and fat crystals and thus affect the mechanical strength of the interfacial film [Ogden & Rosenthal, 1997], while the competitive adsorption of lecithin to displace proteins adsorbed at the surface of fat crystals may facilitate the coalescence of fat globules and thus destabilise the emulsions [Melsen & Walstra, 1989]. The adsorption of lecithin may also change the polarity of fat crystals [Johansson & Bergenståhl, 1992;Rousseau, 2000]. Usually, low-molecular-weight surfactants are effective at generating emulsions with smaller droplets because of their fast adsorption to the newly created interfaces, but they may not be effective at providing long-term stability to the emulsions.…”
Section: Use Of Soy Lecithin In Combination With Other Additivesmentioning
confidence: 99%
“…The degree of agglomeration can be followed by measuring the particle size of the particles directly or inferred from apparent viscosity measurements [1,5] or from sedimentation measurements [4]. For studies of agglomerates formed by weak adhesion, sedimentation experiments are more suitable than rheological measurements as the forces applied to the aggregate during measurement are less [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chevalley [3] showed that the presence of 3-4% water increases the viscosity of molten chocolate markedly as compared to the typical moisture concentrations of 0.5-1.5%. Emulsifiers can assist the dispersion of fine particles by adsorbing at the surface and providing some steric repulsion [4].…”
Section: Introductionmentioning
confidence: 99%
“…When a small proportion of a secondary immiscible liquid such as water or glycerol is added to a suspension of this kind, it can lead to behavioural changes from a fluid-like material to a paste-like material (Koos and Willenbacher, 2011;Johansson and Bergenståhl, 1992). This transformation has been ascribed to the formation of liquid bridges between the solid particles by the secondary liquid thereby modifying the rheological properties of the suspension such as its yield stress and viscosity which can increase several-fold Willenbacher, 2011, 2012; chemical engineering research and design x x x ( 2 0 1 6 ) xxx-xxx mechanisms are responsible for the movement of a secondary liquid phase in a suspension including gravity, capillary and diffusion effects (Ghosh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%